Investigating the challenges, benefits, and applications of digital health in South Africa: A PRISMA process - Kgashwane, Tshenolo Eunice; Chukwuere, Joshua Ebere (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2025)
Digital health technologies have the ability to enhance the quality of healthcare. The usage of digital technologies (digital gadgets and their related apps, platforms, and websites) has led to numerous claims in public health and medical research about an impending breakthrough in the health sector, preventative medicine, and public health. Nevertheless, it is crucial to take a more cynical stance when evaluating the effects and consequences of digital health. Moreover, digital health adoption in developing and developed countries has disclosed several advantages, challenges, and applications. Thus, this study aimed to investigate the challenges, benefits, and applications of digital health in South Africa. The methodology utilized in this study was a qualitative systematic review through the PRISMA process and made use of documents such as accredited academic journals, articles, and books to gather data. This study used a sequential sampling method, and data were collected until saturation was reached. For purposes of data analysis, the study used thematic analysis to discover themes from the gathered data. The findings of this study revealed barriers that impede digital health adoption in South Africa. These barriers include technical, supportive policies, skilled manpower, and many more. Furthermore, work is needed to explore how the adoption of digital health technologies will affect the work of individuals. It is recommended that end users be trained on how to use digital health systems and many other things.